PENGARUH KOMPOSISI TEPUNG JAGUNG DAN MOLASE PADA MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL JAMUR TIRAM PUTIH - Gustian Gustian; Agustina Listiawati; Tantri Palupi (Fakultas Pertanian, Universitas Janabadra, 2023)
White oyster mushroom is a plant that is currently widely cultivated. However, in Indonesia, especially in West Kalimantan, its productivity is still very narrow to fulfill market demand. Efforts that can be made to increase the production of white oyster mushrooms can be done by adding nutrients in the form of corn flour and molasses to the white oyster mushroom baglog media. This study aims to obtain the best media composition for the growth and yield of white oyster mushrooms. The design used in this study was a completely randomized design field experiment with nine levels of combination treatment of corn flour and molasses. each treatment was repeat with three replicaty, each replication consisted of four baglog samples. combination of corn flour (%) and molasses (ml) namely p1 = 90% basic material +10% corn flour + 10 ml molasses; p2 = 90% basic material + 10% corn flour + 20 ml molasses; p3 =90% basic material + 10% corn flour + 30 ml molasses; p4 = 85% basic material + 15% corn flour + 10 ml molasses; p5 = 85% basic material + 15% corn flour + 20 ml molasses; p6 = 85% basic material + 15% corn flour + 30 ml molasses; p7 = 80% basic material + 20% corn flour + 10 ml molasses; p8 = 80% basic material + 20% corn flour + 20 ml molasses; and p9 = 80% basic material + 20% corn flour + 30 ml molasses. Variable observed included age from harvest, the diameter of the hood, number of hoods per baglog, and fresh weight per baglog. The results showed that the combination of 20% corn flour + 10 ml molasses gave the best yield to increase fresh weight per baglog and harvesting age.INTISARISalah satu usaha yang dapat dilakukan untuk meningkatkkan produksi jamur tiram putih adalah dengan cara menambahkan nutrisi berupa tepung jagung dan molase pada media baglog jamur tiram putih tersebut. Penelitian ini bertujuan untuk mendapatkan komposisi media terbaik untuk pertumbuhan dan hasil jamur tiram putih. Rancangan yang digunakan dalam penelitian ini adalah eksperimen lapangan Rancangan Acak Lengkap dengan sembilan taraf perlakuan kombinasi tepung jagung dan molase. Masing-masing perlakuan diulang sebanyak tiga kali, setiap ulangan terdiri dari empat sampel baglog. Kombinasi tepung jagung (%) dan molase (ml) yang dimaksud yaitu : p1 = 90% bahan dasar + 10 % tepung jagung + 10 ml molase; p2 = 90% bahan dasar + 10 % tepung jagung + 20 ml molase; p3 = 90% bahan dasar + 10% tepung jagung + 30 ml molase; p4 = 85% bahan dasar + 15% tepung jagung + 10 ml molase; p5 = 85% bahan dasar + 15% tepung jagung + 20 ml molase; p6 = 85% bahan dasar + 15% tepung jagung + 30 ml molase; p7 = 80% bahan dasar + 20% tepung jagung + 10 ml molase; p8 = 80% bahan dasar + 20% tepung jagung + 20 ml molase; dan p9 = 80% bahan dasar + 20% tepung jagung + 30 ml molase. Variabel yang diamati meliputi umur mulai panen, diameter tudung, jumlah tudung, dan berat segar per baglog. Hasil penelitian menunjukan bahwa kombinasi 20% tepung jagung + 10 ml molase memberikan hasil yang terbaik untuk berat segar per baglog dan umur mulai panen.